Distribution of plastic, reconstructive and aesthetic surgery professionals in Turkey: According to provinces - SAÇAK, BÜLENT (My University, 2014)
Plastic, Reconstructive and Aesthetic Surgery (PRAS) is a unique surgical specialty because of its broad area of expertise and its tendency for multidisciplinary work. In this study, through the cross-sectional data obtained from Turkish Statistical Institute and the Ministry of Health, ratios of plastic surgery professionals per population in each province in Turkey has been calculated and compared. The overall ratio of PRAS professionals per 100,000 populations is 1.05 in Turkey. In the analysis made according to the provinces, the highest ratio of PRAS professionals has been found in Ankara (1.99/100,000). In the highly populated cities, PRAS professional ratio is 1.2 in average, whereas the same ratio is 0.7 in average in low-population cities (p<0.001). Based on the results of the present study, the distribution of PRAS professionals in Turkey shows a great diversity across the provinces. The results of this cross-sectional, descriptive, original study are very valuable in terms of keeping a light on health and education policies regarding plastic and reconstructive surgery.
Türkiye'de plastik rekonstrüktif ve estetik cerrahi: Uzman hekimlerinin illere göre dağılımı
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Surgery Medicine Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery; Turkey; plastic surgery; professionals; distribution according to provinces; distribution according to regions